2015
DOI: 10.1093/ijnp/pyv044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Atomoxetine on the Cognitive Functions in Treatment of Attention Deficit Hyperactivity Disorder in Children with Congenital Hypothyroidism: A Pilot Study

Abstract: Background:With early initiation of thyroxine supplementation, children with congenital hypothyroidism (CH) retain some subtle deficits, such as attention and inhibitory control problems. This study assessed the effects of atomoxetine on cognitive functions in treatment of attention deficit hyperactivity disorder (ADHD) symptoms in children with CH.Methods:In a 6-month, open-labeled pilot study, 12 children were recruited and received atomoxetine. The measures of efficacy were scores on the Swanson, Nolan and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
(21 reference statements)
1
10
0
Order By: Relevance
“…We used the SNAP-IV to measure specific ADHD symptoms and ODD symptoms separately. As the SNAP-IV is a frequently used measure in ADHD studies (e.g., [31][32][33][34]), comparison with other trials and samples may be possible. (3) Internalizing problems were assessed with the Internalizing subscale of the Child Behavior Checklist (CBCL) [35].…”
Section: Methodsmentioning
confidence: 99%
“…We used the SNAP-IV to measure specific ADHD symptoms and ODD symptoms separately. As the SNAP-IV is a frequently used measure in ADHD studies (e.g., [31][32][33][34]), comparison with other trials and samples may be possible. (3) Internalizing problems were assessed with the Internalizing subscale of the Child Behavior Checklist (CBCL) [35].…”
Section: Methodsmentioning
confidence: 99%
“…The Wechsler Intelligence Scale for Children-IV (WISC-IV) was used in this study as a measure of participants' IQ. The Chinese version of the WISC-IV is the most popular and widely researched test for children's intelligence; the test also has good reliability and validity (Yang, Gao, Li, & Zhao, 2015). It incorporates a collection of 13 distinct subtests in two scales: verbal and performance scales.…”
Section: Methodsmentioning
confidence: 99%
“…However, although early screening programs for CH have proven effective in reducing intellectual disability, the key issue is identifying neurocognitive sequelae, even the subtlest ones, which may persist despite early treatment (2,(4)(5)(6)9,11,19) . Studies have reported that individuals with CH may present attention, memory, visuocognitive, visuospatial and psychomotor disorders (1,10,12,14,(18)(19)(20)24) . Yang et al (24) demonstrated that children with CH are more likely to present symptoms of attention-deficit hyperactivity disorder (ADHD).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that individuals with CH may present attention, memory, visuocognitive, visuospatial and psychomotor disorders (1,10,12,14,(18)(19)(20)24) . Yang et al (24) demonstrated that children with CH are more likely to present symptoms of attention-deficit hyperactivity disorder (ADHD). In this study, the parents of the individuals in the EG reported that their children presented inattention as well as agitation and/or hyperactivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation